Bioorthogonal Coordination Polymer Nanoparticles with Aggregation‐Induced Emission for Deep Tumor‐Penetrating Radio‐ and Radiodynamic Therapy. Issue 9 (25th January 2021) - Liu, Jingjing; Hu, Fang; Wu, Min; Tian, Longlong; Gong, Fei; Zhong, Xiaoyan; Chen, Muchao; Liu, Zhuang; Liu, Bin
Abstract: Radiodynamic therapy (RDT), an emerging therapeutic approach for cancer treatment by employing ionizing irradiation to induce localized photodynamic therapy (PDT) can overcome the drawbacks of the limited penetration depth for traditional PDT and the unconcentrated energy in the tumor for traditional radiotherapy (RT). Taking advantage of aggregation‐induced emission (AIE) photosensitizers with bright fluorescence and efficient singlet oxygen production in the aggregate state, Hf‐AIE coordination polymer nanoparticles (CPNs), which show both strong RT and RDT effect under X‐ray irradiation, are developed. Furthermore, to enhance the tumor accumulation and prolong the tumor retention of the CPNs, bioorthogonal click chemistry is applied in the system through coupling between dibenzocyclooctyne (DBCO)‐modified CPNs (Hf‐AIE‐PEG‐DBCO) (PEG: poly(ethylene glycol)) and azide groups on the cell membrane formed by metabolic glycoengineering. Thanks to the high penetration of X‐ray irradiation, the bioorthogonal‐assisted RT and RDT combination therapy realizes significant killing of cancer cells without showing noticeable biotoxicity after intravenous administration of CPNs. Abstract : Coordination polymer nanoparticles constructed from a photosensitizer with aggregation‐induced emission property (AIE PS) and the high‐ Z element hafnium (Hf) is fabricated through a solvothermal method. After PEGylation followed by bioorthogonal click chemistry, Hf‐AIE‐PEG‐DBCO (PEG: poly(ethylene glycol); DBCO: dibenzocyclooctyne) can react on the surface of tumor cells to realize deep tumor‐penetrating radiotherapy and radiodynamic therapy with enhanced tumor accumulation and extended tumor retention.